Parametrische Darstellung der Nierenfunktion mit 99mTC-Merkaptoazetyltriglyzin (MAG3) - Szabö, Z.; Kutkuhn, B.; Georgescu, G.; Mecklenbeck, W.; Suatmadji, A.; Vosberg, H. (Nuklearmedizin - NuclearMedicine, 1989)
99mTc-mercaptoacetyltriglycine (MAG3) has recently been introduced for imaging kidney function. Due to the much lower radiation dose per MBq, the total administered activity can be much higher than in the case of 131l-ortho-iodo-hippurate (OIH). The improved counting statistics make this tracer useful for parametric imaging of the kidneys. To investigate this potential of MAG3, its kinetics was compared with that of the reference tracer OIH in 38 patients. Parameters of extrarenal tracer kinetics such as the distribution volumes, the whole-body elimination times and the clearance rates showed a good correlation; however, the clearance rate of MAG3 was always lower than that of OIH. The intrarenal kinetics was investigated using the transfer function which was calculated by deconvolution analysis of the renographic curves. Parameters of the transfer function such as the amplitude, extraction fraction and mean transport time demonstrated a high correlation between the two tracers. Since MAG3 seems to be suitable for parametric imaging of kidney function, parametric images of perfusion, uptake, extraction and transport times were calculated by deconvolution analysis of the MAG3 pixel-renograms in various renal disorders. The parameters were distributed homogenously throughout the parenchyma of normal kidneys. In a kidney with a hemodynamically significant renal artery stenosis the perfusion parameter was decreased and the time parameter was prolonged. Further examples of a renal graft acute tubular necrosis, an obstructive uropathy, an obstructive nephropathy and of a horse-shoe kidney demonstrate that the parametric images are useful for quantitative investigation of regional renal function.